Analysis of the p53/CEP-1 regulated non-coding transcriptome in C. elegans by an NSR-seq strategy. Issue 10 (21st May 2014) - Xu, Derong; Wei, Guifeng; Lu, Ping; Luo, Jianjun; Chen, Xiaomin; Skogerbø, Geir; Chen, Runsheng
Abstract: In recent years, large numbers of non-coding RNAs (ncRNAs) have been identified in C. elegans but their functions are still not well studied. In C. elegans, CEP -1 is the sole homolog of the p53 family of genes. In order to obtain transcription profiles of ncRNAs regulated by CEP-1 under normal and UV stressed conditions, we applied the 'not-so-random' hexamers priming strategy to RNA sequencing in C. elegans, This NSR-seq strategy efficiently depleted rRNA transcripts from the samples and showed high technical replicability. We identified more than 1, 000 ncRNAs whose apparent expression was repressed by CEP-1, while around 200 were activated. Around 40% of the CEP-1 activated ncRNAs promoters contain a putative CEP-1-binding site. CEP-1 regulated ncRNAs were frequently clustered and concentrated on the X chromosome. These results indicate that numerous ncRNAs are involved in CEP-1 transcriptional network and that these are especially enriched on the X chromosome in C. elegans .